Preparation of superoxide dismutase loaded chitosan microspheres: Characterization and release studies - Akbuğa, Fatma Jülide; ÇELİK, ÖZGE (Elsevier, 2007)
Superoxide dismutase (SOD) is the most potent antioxidant enzyme. In this study, SOD was encapsulated in chitosan microspheres to obtain suitable sustained protein delivery. Protein-loaded chitosan microspheres with various formulations were prepared based on complex coacervation process. Due to the inherent characteristic of SOD, high encapsulation efficiency could not be obtained with simple preparation method. The pH of chitosan solution is 3.0; when the chitosan microspheres were prepared with this solution, encapsulation was low. Therefore, several strategies have been tested to increase the encapsulation efficiency and good results have been obtained. 70–80% protein encapsulation efficiency was obtained. The addition of PEG to the protein solution enhanced the encapsulation efficiency also. Mean sizes of microspheres were between 1.38 and 1.94 μm. Factors affecting the release behaviour of SOD from microspheres have been studied. They included pH values of chitosan solution (the pH of chitosan solution is 3.0), addition of PEG to the protein solution and the use of adsorption technique. In general, biphasic release profiles were obtained with these formulations. The protein activity changed between 70 and 100% during the release. In general, the protein activity remained in acceptable limits. The SOD encapsulated chitosan microspheres can be prepared by changing the pH or addition of PEG, allowing the safe incorporation of protein for controlled release.
Keywords: Chitosan; Superoxide dismutase; Microspheres; PEG; Controlled release; Protein